Measuring proton shift tensors with ultrafast MAS NMR - Miah, Habeeba K.; Bennett, David A.; Iuga, Dinu; Titman, Jeremy J. (Elsevier, 2013)
A new proton anisotropic-isotropic shift correlation experiment is described which operates with ultrafast MAS, resulting in good resolution of isotropic proton shifts in the detection dimension. The new experiment makes use of a recoupling sequence designed using symmetry principles which reintroduces the proton chemical shift anisotropy in the indirect dimension. The experiment has been used to measure the proton shift tensor parameters for the OH hydrogen-bonded protons in tyrosine.HCl and citric acid at Larmor frequencies of up to 850 MHz.